Optimization of fluoride adsorption from aqueous solution over mesoporous titania‐alumina composites using Taguchi method. (12th December 2021) - Al Mesfer, Mohammed K.; Danish, Mohd; Shah, Mumtaj
Abstract: The optimization of fluoride removal from aqueous media was studied over the mesoporous titania‐alumina composites using Taguchi method‐based L25 orthogonal array experimental design. The chemical structure, surface chemistry, and morphology of as‐prepared composite adsorbents were studied utilizing various analytical methods. The findings of the characterization demonstrated that the produced composites have high textural qualities, which are conducive to enhanced fluoride adsorption. The optimum conditions for maximum percentage removal of fluoride from aqueous solution were found as adsorbent type as TA75, adsorbent dose 4 g L −1, initial concentration of fluoride 40 ppm, solution pH 3 with a treatment time of 60 min. Under the optimum conditions, 98% of fluoride adsorption was achieved. Analysis of variance revealed that the solution pH followed by the adsorbent dose was the most significant for fluoride adsorption. The Langmuir model and pseudo‐second‐order kinetic model fit the adsorption data well, and the TA75 adsorbent had a maximum Langmuir fluoride adsorption capacity of 34.48 mg g −1 at pH = 3. The thermodynamic information suggests that the adsorption was spontaneous and endothermic under the given operating conditions. The synergic combination of Ti–Al nanoparticles demonstrated a high percentage removal of fluoride under the optimized operating conditions. Practitioner Points: The Taguchi method‐based design of the experimental approach was implemented in the fluoride adsorption process. Mesoporous titania‐alumina composites with 0 to 100 wt.% of alumina in titania were prepared and applied to remove fluoride from an aqueous solution. Solution pH was the most influential parameter for the fluoride adsorption process, while the synergistic combination of 75 wt.% alumina in titania showed the maximum adsorption capacity. Abstract : The synthesis of mesoporous Ti‐Al mixed oxide from TIP and AIP and its application in flouride removal from waste water wherein the optimization is done using a L25 Taguchi design. Due to the mopholoical variation in Ti‐Al mixed oxide depending on the composition of oxide, a variation in adsorption capacity is expected.